Numerical simulation for spray spatial distribution of swirl nozzle and its target dustfall area prediction - Cuicui Xu; Xinyu Jia; Jingjing Jing; Junpeng Wang; Qingyi Mi; Gang Zhou; Lirong Wu (Scientific Reports)
Abstract The droplet breakup and distribution of the internal flow field and external spray field of a nozzle were obtained under different pressures. The thickness of the liquid film increased with pressure as a quadratic function. The maximum value of 0.281 mm at 2 MPa decreased to 0.172 mm at 10 MPa, equivalent to 38.8% decrease. The MATLAB was used to obtain the particle size distribution characteristics of the droplets under different pressures. At 2 MPa, droplet breakup dominated the axial interval [0–700 mm]. With the increase of pressure, D50 distribution as a whole continues to decrease, 2–6 MPa change, the particle size reduction is larger, every increase of 2 MPa reduced by about 15%. 6-10 MPa change, the particle size reduction is smaller, every increase of 2 MPa reduced by about 8%. A model to predict the optimal dust reduction areas under varying pressures was developed. The prediction results indicate that at pressures of 5 MPa and 9 MPa, the target dust removal areas were [344 mm, 710 mm] and [424 mm, 942 mm] along the axial direction, respectively.